Інтернаціоналізація освітнього середовища і вітчизняна вища школа - Солоденко, Алла Костянтинівна; Погребняк, Віталій Петрович; Дашковська, Олена Володимирівна (НТУ "ХПІ", 2017)
Аналізуються євроінтеграційні процеси, що відбуваються в сучасному освітньому і науковому середовищі, у тому числі, інтернаціоналізація вищої освіти. Оцінюється значення Болонської декларації у побудові єдиного Європейського простору вищої освіти та ефективність імплементації положень Закону України "Про вищу освіту", актів Уряду і Міністерства освіти і науки України, направлених на реформування вищої школи України, її інтеграцію в міжнародний простір вищої освіти. Наводяться підсумки зробленого за останні роки та прогнозуються подальші кроки щодо модернізації освітнього процесу у вищій школі.

Analyses of European integration processes in the modern educational and scientific community, including the internationalization of higher education. Estimated value of the Bologna Declaration to build a single European higher education area and the effectiveness of the implementation of the provisions of the Law of Ukraine "On higher education", acts of the Government and the Ministry of education and science of Ukraine aimed at reforming the higher school of Ukraine, its integration in the international higher education space. Given the results achieved in recent years and projected further steps on modernization of educational process in higher school.
Internationalization of the educational environment and the national higher school
Keywords: Болонська декларація; мобільність; конкурентність; стандарт вищої освіти; якість вищої освіти; Bologna Declaration; internationalization; mobility; competitiveness; higher education standard; quality of higher education